Stress Alters the Effect of Alcohol on Catecholamine Dynamics in the Basolateral Amygdala - Deal, Alex L.; Park, Jinwoo; Weiner, Jeff L.; Budygin, Evgeny A. (Frontiers in Behavioral Neuroscience, 2021)
The current rodent study applied in vivo fast-scan cyclic voltammetry (FSCV), paired with a pharmacological approach, to measure the release of the catecholamines (CA) dopamine (DA) and norepinephrine (NE) in the basolateral amygdala (BLA) following locus coeruleus (LC) stimulation. The primary goal was to determine if exposure to either social (social defeat) or non-social (forced swim) stress altered LC-evoked catecholamine release dynamics in the BLA. We used idazoxan (α2 adrenergic receptor antagonist) and raclopride (D2 dopamine receptor antagonist) to confirm the presence of NE and DA, respectively, in the measured CA signal. In non-stressed rats, injection of idazoxan, but not raclopride, resulted in a significant increase in the detected CA signal, indicating the presence of NE but not DA. Following exposure to either stress paradigm, the measured CA release was significantly greater after injection of either drug, suggesting the presence of both NE and DA in the LC-induced CA signal after social or non-social stress. Furthermore, acute administration of alcohol significantly decreased the CA signal in stressed rats, while it did not have an effect in naïve animals. Together, these data reveal that, while LC stimulation primarily elicits NE release in the BLA of control animals, both social and non-social stress unmask a novel dopaminergic component of LC catecholamine signaling. Future studies will be needed to identify the specific neural mechanism(s) responsible for these plastic changes in LC-BLA catecholamine signaling and to assess the possible contribution of these changes to the maladaptive behavioral phenotypes that develop following exposure to these stressors.